Identifikasi Alternatif Sumber Air Baku Baru Pdam Tirta Dharma Duri - YR, Habrio Ilva; Siswanto, Siswanto; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Nowadays, the pure water needs of PDAM Tirta dharma Duri is filled by PT CPI. In the dry season, the water supply is decrease cause about 8614 of costumers get lack of water. In content to fulfil the source of pure water so the company did the survey to investigate water resource around Duri to fill water into the company. This study aims to identify the technical proper of pure water from Jurong I, II, III, Petani and Sam-sam river. Quality of water is analyzed by taking the samples from the rivers then they subjected in physic and chemical parametric. Quantity of water is analyzed by Mock method to find the reliable debit with probability 90%.The finding showed that reliable debit of Jurong I, II, III, Petani and Sam-samriver is 0.743 m3/sec, 1.399 m3/sec, 12.824 m3/sec, 0.13m3/sec, and 1.032 m3/sec. water source quality for Jurong I, II, III, Sam- sam river including on class III, and Petani river on class II. Key words: Mock Method, Quantity, Water Source,